MRI features of extraocular muscle metastases compared to those of other extraocular muscle diseases of non-thyroid origin. Issue 12 (December 2022) - Miura, A.; Kashiwagi, N.; Sakai, M.; Hyodo, T.; Takahashi, H.; Miyauchi, Y.; Maenishi, O.; Ishii, K.; Nakanishi, K.; Tomiyama, N.
Abstract : Aim: To identify the magnetic resonance imaging (MRI) features of metastases to the extraocular muscles (EOM metastases). Material and methods: The MRI features of 19 patients with EOM metastases were compared with those of 24 patients with EOM diseases of non-thyroid origin. MRI was used to assess the number of tumours, morphology, signal intensity on T2-weighted images, enhancement patterns, and apparent diffusion coefficient (ADC) values. Results: Single muscular involvement was observed in 10 patients, and multiple muscular involvement was observed in nine patients. The morphology was focally discrete in nine patients, and diffuse infiltrative in 10 patients; all the nine patients with focal discrete morphology presented with single muscular lesions. On T2-weighted images, the signal intensities were intermediate or low in 15 patients and a mixture of high and intermediate in four patients. In 14 patients for whom contrast-enhanced images were available, ring enhancement ( n= 5), heterogeneous diffuse enhancement ( n= 5), and homogeneous enhancement ( n= 4) were seen. The mean ADC value was 0.98 × 10 −3 mm 2 /s. Compared to other EOM diseases of non-thyroid origin, single muscular presentation, focal discrete morphology, the presence of hyperintensity on T2-weighted images, and ring or heterogeneous enhancement were significantly more frequent in EOM metastases. Conclusion: The MRI features of EOM metastases showed two main patterns: a single discrete mass and multiple infiltrative masses. In addition to the presentation as a single discrete mass, the presence of hyperintensity on T2-weighted images and ring or heterogeneous enhancement can aid in the differentiation of EOM metastases from other EOM diseases. Highlights: EOM metastases can present as either a discrete or an infiltrative mass. Solitary discrete presentation is suggestive of EOM metastases. Multiple infiltrative presentation mimics other diseases cause EOM enlargement. Hyperintensity on T2-weighted images can aid in the disease differentiation. Ring or heterogeneous enhancement also can aid in the differentiation.